2010
DOI: 10.1111/j.1651-2227.2010.01685.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, management and mortality of acute hypoxemic respiratory failure and acute respiratory distress syndrome from a prospective study of Chinese paediatric intensive care network

Abstract: In this prospective study, AHRF had high possibilities to develop ARDS and death risk, as impacted by ventilation settings and fluid intake in the early treatment, as well as socioeconomic factors, which should be considered for implementation of standard of care in respiratory therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
38
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 34 publications
(50 reference statements)
9
38
1
1
Order By: Relevance
“…Contrary to our original hypothesis, the prevalence and mortality we found are similar to those reported by other authors, who have found that ARDS develops in approximately 1-4% of children admitted to ICUs and that such patients display mortality that range from 20% to 60% (6-10). We found an overall PICU mortality rate of nearly 40% for patients with ALI/ARDS, and our findings are in agreement with some previous studies (6,9,10,17).…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…Contrary to our original hypothesis, the prevalence and mortality we found are similar to those reported by other authors, who have found that ARDS develops in approximately 1-4% of children admitted to ICUs and that such patients display mortality that range from 20% to 60% (6-10). We found an overall PICU mortality rate of nearly 40% for patients with ALI/ARDS, and our findings are in agreement with some previous studies (6,9,10,17).…”
Section: Discussionsupporting
confidence: 95%
“…The former study included nonintubated patients, and the latter had nearly 20% of patients with respiratory syncytial virus, both facts leading to lower mortality rates. Therefore, our PICU mortality rate likely reflects the characteristics of our patients, the majority of which (85%) had an underlying disease; of note, in several previous studies, patients with chronic illnesses represented only 32-60% of the populations analyzed (7,8,10,17,18). In our study, patient care was left to the discretion of the attending physician, whereas in some studies, there was a predefined ventilation protocol (17,18).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, classification based on either the 24-hour Pao 2 /Fio 2 or the worst Pao 2 / Fio 2 in the first 24 hours better discriminated the outcomes of mortality, VFD = 0 at 28 days, or VFD up to 14 days. The 24-hour Pao 2 /Fio 2 best categorized degree of lung injury, as demonstrated by stepwise fewer VFDs and longer duration of Our ARDS prevalence (5,6,20,21) and severity of illness (4,6,22,23) were similar to prior cohorts, with comparable PRISM III (4, 6) and initial Pao 2 /Fio 2 at ARDS diagnosis (4,23). Our initial PEEP of 10 cm H 2 O (IQR, 8,12) is double that reported by Flori et al (4) and Hu et al (20) and more consistent with Pediatric Acute Lung Injury Epidemiology and Natural History (6) and the Australian/New Zealand cohorts (5), possibly suggesting increasing comfort with higher PEEP in pediatrics.…”
Section: Discussionsupporting
confidence: 56%
“…Then, multivariate Cox's regressions were performed for the same outcomes adjusting for age, sex, PRISM-III 24 , ARDS type (primary/secondary), and study center. These covariates were chosen because of their epidemiological role [4,14] and their association with the outcomes [11,15,16] by unanimous agreement within the working group. BD definition was inserted in the model and considered to have three categories.…”
Section: Statisticsmentioning
confidence: 99%